Let me be very clear: math is all about practice, and there are no shortcuts. So, please refer to B. S. Grewal's book for theory and practice questions.
Here, I can only provide video links to help you understand the topic.π
If for each value of the complex variable z = ( x + i y ) z = (x + iy) z = ( x + i y ) in a given region R, we have one or more values of w ( = u + i v ) w (= u + iv) w ( = u + i v ) , then w w w is said to be a complex function of z and we write w = u ( x , y ) + i v ( x , y ) = f ( z ) w = u(x, y) + iv(x, y) = f(z) w = u ( x , y ) + i v ( x , y ) = f ( z ) where u , v u, v u , v are real functions of x and y.
If to each value of z, there corresponds one and only one value of w, then w is said to be a single-valued function of z otherwise a multi-valued function.
For example, w = 1 z w = \frac{1}{z} w = z 1 β is a single-valued function and w = z w = \sqrt{z} w = z β is a multi-valued function of z.
The former is defined at all points of the z-plane except at z = 0 and the latter assumes two values for each value of z except at z = 0.
VIDEO
Please click here if you can't watch video.
Exponential Function:
When x is real, we are already familiar with the exponential function
e x = 1 + x 1 ! + x 2 2 ! + β― + x n n ! + β¦ β . e^x = 1 + \frac{x}{1!} + \frac{x^2}{2!} + \dots + \frac{x^n}{n!} + \dots \infty. e x = 1 + 1 ! x β + 2 ! x 2 β + β― + n ! x n β + β¦ β.
Similarly, we define the exponential function of the complex variable z = x + i y z = x + iy z = x + i y , as
e z Β orΒ exp β‘ ( z ) = 1 + z 1 ! + z 2 2 ! + β― + z n n ! + β¦ β . (i) e^z \text{ or } \exp(z) = 1 + \frac{z}{1!} + \frac{z^2}{2!} + \dots + \frac{z^n}{n!} + \dots \infty. \quad \quad \text{(i)} e z Β orΒ exp ( z ) = 1 + 1 ! z β + 2 ! z 2 β + β― + n ! z n β + β¦ β. (i)
Properties:
Exponential form of z = r e i ΞΈ z = re^{i \theta} z = r e i ΞΈ
Putting x = 0 in (i), we get,
e i y = 1 + i y 1 ! + ( i y ) 2 2 ! + ( i y ) 3 3 ! + ( i y ) 4 4 ! + β¦ β e^{iy} = 1 + \frac{iy}{1!} + \frac{(iy)^2}{2!} + \frac{(iy)^3}{3!} + \frac{(iy)^4}{4!} + \dots \infty e i y = 1 + 1 ! i y β + 2 ! ( i y ) 2 β + 3 ! ( i y ) 3 β + 4 ! ( i y ) 4 β + β¦ β
= ( 1 β y 2 2 ! + y 4 4 ! β β¦ β ) + i ( y β y 3 3 ! + y 5 5 ! β β¦ β ) = cos β‘ y + i sin β‘ y = \left( 1 - \frac{y^2}{2!} + \frac{y^4}{4!} - \dots \right) + i \left( y - \frac{y^3}{3!} + \frac{y^5}{5!} - \dots \right) = \cos y + i \sin y = ( 1 β 2 ! y 2 β + 4 ! y 4 β β β¦ ) + i ( y β 3 ! y 3 β + 5 ! y 5 β β β¦ ) = cos y + i sin y
Thus,
e z = e x β
e i y = e x ( cos β‘ y + i sin β‘ y ) e^z = e^x \cdot e^{iy} = e^x (\cos y + i \sin y) e z = e x β
e i y = e x ( cos y + i sin y )
Also,
x + i y = r ( cos β‘ ΞΈ + i sin β‘ ΞΈ ) = r e i ΞΈ . Β Thus,Β z = r e i ΞΈ x + iy = r(\cos \theta + i \sin \theta) = re^{i \theta}. \text{ Thus, } z = re^{i \theta} x + i y = r ( cos ΞΈ + i sin ΞΈ ) = r e i ΞΈ . Β Thus,Β z = r e i ΞΈ
e z e^z e z is periodic function having imaginary period 2 Ο i 2 \pi i 2 Οi ; [ e z + 2 n Ο i = e z , β
β e 2 n Ο i = e 0 = e x ] [e^{z + 2n \pi i} = e^z, \; e^{2n \pi i} = e^0 = e^x] [ e z + 2 nΟi = e z , e 2 nΟi = e 0 = e x ]
e z e^z e z is not zero for any value of z.
Since,
e z = e x β
e i y = r e i ΞΈ Β orΒ e x β
e i y = r e i ΞΈ e^z = e^x \cdot e^{i y} = re^{i \theta} \text{ or } e^x \cdot e^{i y} = re^{i \theta} e z = e x β
e i y = r e i ΞΈ Β orΒ e x β
e i y = r e i ΞΈ
Therefore,
r = e x > 0 , β
β y = ΞΈ , β
β β£ e i y β£ = 1 , r = e^x > 0, \; y = \theta, \; |e^{iy}| = 1, r = e x > 0 , y = ΞΈ , β£ e i y β£ = 1 ,
ThusΒ β£ e z β£ = β£ e x β£ , β
β β£ e i y β£ = e x β 0. \text{Thus } |e^z| = |e^x|, \; |e^{iy}| = e^x \neq 0. ThusΒ β£ e z β£ = β£ e x β£ , β£ e i y β£ = e x ξ = 0.
e z βΎ = e z βΎ e^{\overline{z}} = \overline{e^z} e z = e z
Since,
e z βΎ = e x β i y = e x β
e β i y = e x ( cos β‘ y β i sin β‘ y ) e^{\overline{z}} = e^{x - iy} = e^x \cdot e^{-iy} = e^x (\cos y - i \sin y) e z = e x β i y = e x β
e β i y = e x ( cos y β i sin y )
= e x ( cos β‘ y + i sin β‘ y ) = e z = e^x (\cos y + i \sin y) = e^z = e x ( cos y + i sin y ) = e z
Trigonometric functions relate angles in a right triangle to the ratios of the triangle's side lengths.
They are periodic functions and are fundamental in the study of waves, oscillations, and circular motion.
Sine (sin β‘ ΞΈ \sin \theta sin ΞΈ ): Ratio of the length of the opposite side to the hypotenuse.
sin β‘ ΞΈ = opposite hypotenuse \sin \theta = \frac{\text{opposite}}{\text{hypotenuse}} sin ΞΈ = hypotenuse opposite β
Cosine (cos β‘ ΞΈ \cos \theta cos ΞΈ ): Ratio of the length of the adjacent side to the hypotenuse.
cos β‘ ΞΈ = adjacent hypotenuse \cos \theta = \frac{\text{adjacent}}{\text{hypotenuse}} cos ΞΈ = hypotenuse adjacent β
Tangent (tan β‘ ΞΈ \tan \theta tan ΞΈ ): Ratio of the length of the opposite side to the adjacent side.
tan β‘ ΞΈ = sin β‘ ΞΈ cos β‘ ΞΈ = opposite adjacent \tan \theta = \frac{\sin \theta}{\cos \theta} = \frac{\text{opposite}}{\text{adjacent}} tan ΞΈ = c o s ΞΈ s i n ΞΈ β = adjacent opposite β
Cosecant (csc β‘ ΞΈ \csc \theta csc ΞΈ ): Reciprocal of sine.
csc β‘ ΞΈ = 1 sin β‘ ΞΈ = hypotenuse opposite \csc \theta = \frac{1}{\sin \theta} = \frac{\text{hypotenuse}}{\text{opposite}} csc ΞΈ = s i n ΞΈ 1 β = opposite hypotenuse β
Secant (sec β‘ ΞΈ \sec \theta sec ΞΈ ): Reciprocal of cosine.
sec β‘ ΞΈ = 1 cos β‘ ΞΈ = hypotenuse adjacent \sec \theta = \frac{1}{\cos \theta} = \frac{\text{hypotenuse}}{\text{adjacent}} sec ΞΈ = c o s ΞΈ 1 β = adjacent hypotenuse β
Cotangent (cot β‘ ΞΈ \cot \theta cot ΞΈ ): Reciprocal of tangent.
cot β‘ ΞΈ = 1 tan β‘ ΞΈ = cos β‘ ΞΈ sin β‘ ΞΈ = adjacent opposite \cot \theta = \frac{1}{\tan \theta} = \frac{\cos \theta}{\sin \theta} = \frac{\text{adjacent}}{\text{opposite}} cot ΞΈ = t a n ΞΈ 1 β = s i n ΞΈ c o s ΞΈ β = opposite adjacent β
Key Trigonometric Identities:
Pythagorean Identity:
sin β‘ 2 ΞΈ + cos β‘ 2 ΞΈ = 1 \sin^2 \theta + \cos^2 \theta = 1 sin 2 ΞΈ + cos 2 ΞΈ = 1
Angle Sum and Difference Formulas:
sin β‘ ( a Β± b ) = sin β‘ a cos β‘ b Β± cos β‘ a sin β‘ b \sin(a \pm b) = \sin a \cos b \pm \cos a \sin b sin ( a Β± b ) = sin a cos b Β± cos a sin b
cos β‘ ( a Β± b ) = cos β‘ a cos β‘ b β sin β‘ a sin β‘ b \cos(a \pm b) = \cos a \cos b \mp \sin a \sin b cos ( a Β± b ) = cos a cos b β sin a sin b
tan β‘ ( a Β± b ) = tan β‘ a Β± tan β‘ b 1 β tan β‘ a tan β‘ b \tan(a \pm b) = \frac{\tan a \pm \tan b}{1 \mp \tan a \tan b} tan ( a Β± b ) = 1 β t a n a t a n b t a n a Β± t a n b β
Double Angle Formulas:
sin β‘ 2 ΞΈ = 2 sin β‘ ΞΈ cos β‘ ΞΈ \sin 2\theta = 2 \sin \theta \cos \theta sin 2 ΞΈ = 2 sin ΞΈ cos ΞΈ
cos β‘ 2 ΞΈ = cos β‘ 2 ΞΈ β sin β‘ 2 ΞΈ = 2 cos β‘ 2 ΞΈ β 1 = 1 β 2 sin β‘ 2 ΞΈ \cos 2\theta = \cos^2 \theta - \sin^2 \theta = 2 \cos^2 \theta - 1 = 1 - 2 \sin^2 \theta cos 2 ΞΈ = cos 2 ΞΈ β sin 2 ΞΈ = 2 cos 2 ΞΈ β 1 = 1 β 2 sin 2 ΞΈ
tan β‘ 2 ΞΈ = 2 tan β‘ ΞΈ 1 β tan β‘ 2 ΞΈ \tan 2\theta = \frac{2 \tan \theta}{1 - \tan^2 \theta} tan 2 ΞΈ = 1 β t a n 2 ΞΈ 2 t a n ΞΈ β
Pradeep Giri Academy Perfect Computer Engineer
VIDEO It is not a single video but a playlist, and it contains two videos. When one video finishes, the next will play automatically.
Hyperbolic Function:
If x be real or complex,
(i) e x β e β x 2 \frac{e^x - e^{-x}}{2} 2 e x β e β x β is defined as hyperbolic sine of x and is written as sinh β‘ x \sinh x sinh x .
sinh β‘ x = e x β e β x 2 \sinh x = \frac{e^x - e^{-x}}{2} sinh x = 2 e x β e β x β
(ii) e x + e β x 2 \frac{e^x + e^{-x}}{2} 2 e x + e β x β is defined as hyperbolic cosine of x and is written as cosh β‘ x \cosh x cosh x .
cosh β‘ x = e x + e β x 2 \cosh x = \frac{e^x + e^{-x}}{2} cosh x = 2 e x + e β x β
Thus, sinh β‘ x = e x β e β x 2 \sinh x = \frac{e^x - e^{-x}}{2} sinh x = 2 e x β e β x β and cosh β‘ x = e x + e β x 2 \cosh x = \frac{e^x + e^{-x}}{2} cosh x = 2 e x + e β x β .
Also we define,
tanh β‘ x = sinh β‘ x cosh β‘ x = e x β e β x e x + e β x , coth β‘ x = 1 tanh β‘ x = e x + e β x e x β e β x \tanh x = \frac{\sinh x}{\cosh x} = \frac{e^x - e^{-x}}{e^x + e^{-x}}, \quad \coth x = \frac{1}{\tanh x} = \frac{e^x + e^{-x}}{e^x - e^{-x}} tanh x = c o s h x s i n h x β = e x + e β x e x β e β x β , coth x = t a n h x 1 β = e x β e β x e x + e β x β
sech β‘ x = 1 cosh β‘ x = 2 e x + e β x , cosech β‘ x = 1 sinh β‘ x = 2 e x β e β x \operatorname{sech} x = \frac{1}{\cosh x} = \frac{2}{e^x + e^{-x}}, \quad \operatorname{cosech} x = \frac{1}{\sinh x} = \frac{2}{e^x - e^{-x}} sech x = c o s h x 1 β = e x + e β x 2 β , cosech x = s i n h x 1 β = e x β e β x 2 β
Properties:
Periodic functions: sinh β‘ z \sinh z sinh z and cosh β‘ z \cosh z cosh z are periodic functions having imaginary period 2 Ο i 2\pi i 2 Οi .
sinh β‘ ( z + 2 Ο i ) = sinh β‘ z ; cosh β‘ ( z + 2 Ο i ) = cosh β‘ z \sinh(z + 2\pi i) = \sinh z ; \quad \cosh(z + 2\pi i) = \cosh z sinh ( z + 2 Οi ) = sinh z ; cosh ( z + 2 Οi ) = cosh z
Even and odd functions: cosh β‘ z \cosh z cosh z is an even function while sinh β‘ z \sinh z sinh z is an odd function.
sinh β‘ 0 = 0 \sinh 0 = 0 sinh 0 = 0 , cosh β‘ 0 = 1 \cosh 0 = 1 cosh 0 = 1 , tanh β‘ 0 = 0 \tanh 0 = 0 tanh 0 = 0 .
Relations between hyperbolic and circular functions.
Since for all values of \theta ,
sin β‘ ΞΈ = e i ΞΈ β e β i ΞΈ 2 i and cos β‘ ΞΈ = e i ΞΈ + e β i ΞΈ 2 \sin \theta = \frac{e^{i\theta} - e^{-i\theta}}{2i} \quad \text{and} \quad \cos \theta = \frac{e^{i\theta} + e^{-i\theta}}{2} sin ΞΈ = 2 i e i ΞΈ β e β i ΞΈ β and cos ΞΈ = 2 e i ΞΈ + e β i ΞΈ β
Therefore, putting ΞΈ = i x \theta = ix ΞΈ = i x , we have
sin β‘ i x = e β x β e x 2 i = β ( e x β e β x ) 2 i = i sinh β‘ x \sin ix = \frac{e^{-x} - e^x}{2i} = \frac{-(e^x - e^{-x})}{2i} = i \sinh x sin i x = 2 i e β x β e x β = 2 i β ( e x β e β x ) β = i sinh x
cos β‘ i x = e β x + e x 2 = cosh β‘ x \cos ix = \frac{e^{-x} + e^x}{2} = \cosh x cos i x = 2 e β x + e x β = cosh x
sinh β‘ i x = i sin β‘ x ...Β (i) \sinh ix = i \sin x \quad \text{... (i)} sinh i x = i sin x ...Β (i)
cosh β‘ i x = cos β‘ x ...Β (ii) \cosh ix = \cos x \quad \text{... (ii)} cosh i x = cos x ...Β (ii)
tanh β‘ i x = i tan β‘ x ...Β (iii) \tanh ix = i \tan x \quad \text{... (iii)} tanh i x = i tan x ...Β (iii)
sinh β‘ i x = i sin β‘ x ...Β (iv) \sinh ix = i \sin x \quad \text{... (iv)} sinh i x = i sin x ...Β (iv)
cosh β‘ i x = cos β‘ x ...Β (v) \cosh ix = \cos x \quad \text{... (v)} cosh i x = cos x ...Β (v)
tanh β‘ i x = i tan β‘ x ...Β (vi) \tanh ix = i \tan x \quad \text{... (vi)} tanh i x = i tan x ...Β (vi)
Inverse trigonometric functions are the inverses of the basic trigonometric functions: sine, cosine, tangent, cosecant, secant, and cotangent.
They are used to find angles when the trigonometric values are known.
Definitions:
If y = sin β‘ β 1 x y = \sin^{-1} x y = sin β 1 x , then sin β‘ y = x \sin y = x sin y = x for β Ο 2 β€ y β€ Ο 2 -\frac{\pi}{2} \leq y \leq \frac{\pi}{2} β 2 Ο β β€ y β€ 2 Ο β
If y = cos β‘ β 1 x y = \cos^{-1} x y = cos β 1 x , then cos β‘ y = x \cos y = x cos y = x for 0 β€ y β€ Ο 0 \leq y \leq \pi 0 β€ y β€ Ο
If y = tan β‘ β 1 x y = \tan^{-1} x y = tan β 1 x , then tan β‘ y = x \tan y = x tan y = x for β Ο 2 < y < Ο 2 -\frac{\pi}{2} < y < \frac{\pi}{2} β 2 Ο β < y < 2 Ο β
If y = csc β‘ β 1 x y = \csc^{-1} x y = csc β 1 x , then csc β‘ y = x \csc y = x csc y = x for β Ο 2 β€ y β€ Ο 2 , y β 0 -\frac{\pi}{2} \leq y \leq \frac{\pi}{2}, y \neq 0 β 2 Ο β β€ y β€ 2 Ο β , y ξ = 0
If y = sec β‘ β 1 x y = \sec^{-1} x y = sec β 1 x , then sec β‘ y = x \sec y = x sec y = x for 0 β€ y β€ Ο , y β Ο 2 0 \leq y \leq \pi, y \neq \frac{\pi}{2} 0 β€ y β€ Ο , y ξ = 2 Ο β
If y = cot β‘ β 1 x y = \cot^{-1} x y = cot β 1 x , then cot β‘ y = x \cot y = x cot y = x for 0 < y < Ο 0 < y < \pi 0 < y < Ο
Principal Values:
The principal values for inverse trigonometric functions are as follows:
sin β‘ β 1 x β [ β Ο 2 , Ο 2 ] \sin^{-1} x \in \left[-\frac{\pi}{2}, \frac{\pi}{2}\right] sin β 1 x β [ β 2 Ο β , 2 Ο β ]
cos β‘ β 1 x β [ 0 , Ο ] \cos^{-1} x \in \left[0, \pi\right] cos β 1 x β [ 0 , Ο ]
tan β‘ β 1 x β ( β Ο 2 , Ο 2 ) \tan^{-1} x \in \left(-\frac{\pi}{2}, \frac{\pi}{2}\right) tan β 1 x β ( β 2 Ο β , 2 Ο β )
csc β‘ β 1 x β [ β Ο 2 , Ο 2 ] Β whereΒ y β 0 \csc^{-1} x \in \left[-\frac{\pi}{2}, \frac{\pi}{2}\right] \text{ where } y \neq 0 csc β 1 x β [ β 2 Ο β , 2 Ο β ] Β whereΒ y ξ = 0
sec β‘ β 1 x β [ 0 , Ο ] Β whereΒ y β Ο 2 \sec^{-1} x \in \left[0, \pi\right] \text{ where } y \neq \frac{\pi}{2} sec β 1 x β [ 0 , Ο ] Β whereΒ y ξ = 2 Ο β
cot β‘ β 1 x β ( 0 , Ο ) \cot^{-1} x \in \left(0, \pi\right) cot β 1 x β ( 0 , Ο )
Properties:
Reciprocal Identities:
sin β‘ β 1 x = csc β‘ β 1 1 x , cos β‘ β 1 x = sec β‘ β 1 1 x , tan β‘ β 1 x = cot β‘ β 1 1 x \sin^{-1} x = \csc^{-1} \frac{1}{x}, \quad \cos^{-1} x = \sec^{-1} \frac{1}{x}, \quad \tan^{-1} x = \cot^{-1} \frac{1}{x} sin β 1 x = csc β 1 x 1 β , cos β 1 x = sec β 1 x 1 β , tan β 1 x = cot β 1 x 1 β
Sum and Difference Formulas:
sin β‘ β 1 x + cos β‘ β 1 x = Ο 2 \sin^{-1} x + \cos^{-1} x = \frac{\pi}{2} sin β 1 x + cos β 1 x = 2 Ο β
tan β‘ β 1 x + cot β‘ β 1 x = Ο 2 \tan^{-1} x + \cot^{-1} x = \frac{\pi}{2} tan β 1 x + cot β 1 x = 2 Ο β
sec β‘ β 1 x + csc β‘ β 1 x = Ο 2 \sec^{-1} x + \csc^{-1} x = \frac{\pi}{2} sec β 1 x + csc β 1 x = 2 Ο β
Negative Argument Identities:
sin β‘ β 1 ( β x ) = β sin β‘ β 1 ( x ) \sin^{-1}(-x) = -\sin^{-1}(x) sin β 1 ( β x ) = β sin β 1 ( x )
cos β‘ β 1 ( β x ) = Ο β cos β‘ β 1 ( x ) \cos^{-1}(-x) = \pi - \cos^{-1}(x) cos β 1 ( β x ) = Ο β cos β 1 ( x )
tan β‘ β 1 ( β x ) = β tan β‘ β 1 ( x ) \tan^{-1}(-x) = -\tan^{-1}(x) tan β 1 ( β x ) = β tan β 1 ( x )
Double Angle Formulas:
For values β£ x β£ < 1 |x| < 1 β£ x β£ < 1 ,
2 sin β‘ β 1 x = sin β‘ β 1 ( 2 x 1 β x 2 ) 2 \sin^{-1} x = \sin^{-1} (2x \sqrt{1 - x^2}) 2 sin β 1 x = sin β 1 ( 2 x 1 β x 2 β )
2 tan β‘ β 1 x = tan β‘ β 1 ( 2 x 1 β x 2 ) 2 \tan^{-1} x = \tan^{-1} \left(\frac{2x}{1 - x^2}\right) 2 tan β 1 x = tan β 1 ( 1 β x 2 2 x β )
Derivatives:
d d x sin β‘ β 1 x = 1 1 β x 2 , β£ x β£ < 1 \frac{d}{dx} \sin^{-1} x = \frac{1}{\sqrt{1 - x^2}}, \quad |x| < 1 d x d β sin β 1 x = 1 β x 2 β 1 β , β£ x β£ < 1
d d x cos β‘ β 1 x = β 1 1 β x 2 , β£ x β£ < 1 \frac{d}{dx} \cos^{-1} x = -\frac{1}{\sqrt{1 - x^2}}, \quad |x| < 1 d x d β cos β 1 x = β 1 β x 2 β 1 β , β£ x β£ < 1
d d x tan β‘ β 1 x = 1 1 + x 2 , x β R \frac{d}{dx} \tan^{-1} x = \frac{1}{1 + x^2}, \quad x \in \mathbb{R} d x d β tan β 1 x = 1 + x 2 1 β , x β R
d d x csc β‘ β 1 x = β 1 β£ x β£ x 2 β 1 , β£ x β£ > 1 \frac{d}{dx} \csc^{-1} x = -\frac{1}{|x|\sqrt{x^2 - 1}}, \quad |x| > 1 d x d β csc β 1 x = β β£ x β£ x 2 β 1 β 1 β , β£ x β£ > 1
d d x sec β‘ β 1 x = 1 β£ x β£ x 2 β 1 , β£ x β£ > 1 \frac{d}{dx} \sec^{-1} x = \frac{1}{|x|\sqrt{x^2 - 1}}, \quad |x| > 1 d x d β sec β 1 x = β£ x β£ x 2 β 1 β 1 β , β£ x β£ > 1
d d x cot β‘ β 1 x = β 1 1 + x 2 , x β R \frac{d}{dx} \cot^{-1} x = -\frac{1}{1 + x^2}, \quad x \in \mathbb{R} d x d β cot β 1 x = β 1 + x 2 1 β , x β R
VIDEO
Inverse Hyperbolic Function:
If sinh β‘ u = z \sinh u = z sinh u = z , then u u u is called the hyperbolic sine inverse of z z z and is written as u = sinh β‘ β 1 z u = \sinh^{-1} z u = sinh β 1 z . Similarly, we define cosh β‘ β 1 z \cosh^{-1} z cosh β 1 z , tanh β‘ β 1 z \tanh^{-1} z tanh β 1 z , etc.
The inverse hyperbolic functions, like other inverse functions, are many-valued, but we shall consider only their principal values.
(i) sinh β‘ β 1 z = log β‘ [ z + z 2 + 1 ] \sinh^{-1} z = \log [z + \sqrt{z^2 + 1}] sinh β 1 z = log [ z + z 2 + 1 β ]
(ii) cosh β‘ β 1 z = log β‘ [ z + ( z 2 β 1 ) ] \cosh^{-1} z = \log [z + \sqrt{(z^2 - 1)}] cosh β 1 z = log [ z + ( z 2 β 1 ) β ]
(iii) tanh β‘ β 1 z = 1 2 log β‘ ( 1 + z 1 β z ) \tanh^{-1} z = \frac{1}{2} \log \left( \frac{1+z}{1-z} \right) tanh β 1 z = 2 1 β log ( 1 β z 1 + z β )
(i) Let sinh β‘ β 1 z = u \sinh^{-1} z = u sinh β 1 z = u , then z = sinh β‘ u = 1 2 ( e u β e β u ) z = \sinh u = \frac{1}{2} (e^u - e^{-u}) z = sinh u = 2 1 β ( e u β e β u )
or
2 z = e u β e β u or e 2 u β 2 z e u β 1 = 0 2z = e^u - e^{-u} \quad \text{or} \quad e^{2u} - 2ze^u - 1 = 0 2 z = e u β e β u or e 2 u β 2 z e u β 1 = 0
This being a quadratic in e u e^u e u , we have
e u = 2 z + 4 z 2 + 4 2 = z + z 2 + 1 e^u = \frac{2z + \sqrt{4z^2 + 4}}{2} = z + \sqrt{z^2 + 1} e u = 2 2 z + 4 z 2 + 4 β β = z + z 2 + 1 β
Thus, taking the positive sign only, we have
e u = z + z 2 + 1 or u = log β‘ [ z + z 2 + 1 ] e^u = z + \sqrt{z^2 + 1} \quad \text{or} \quad u = \log \left[ z + \sqrt{z^2 + 1} \right] e u = z + z 2 + 1 β or u = log [ z + z 2 + 1 β ]
Similarly, we can establish (ii).
(iii) Let tanh β‘ β 1 z = u \tanh^{-1} z = u tanh β 1 z = u , then z = tanh β‘ u z = \tanh u z = tanh u
i.e.,
z = e u β e β u e u + e β u z = \frac{e^u - e^{-u}}{e^u + e^{-u}} z = e u + e β u e u β e β u β
Applying componendo and dividendo, we get
1 + z 1 β z = e 2 u \frac{1+z}{1-z} = e^{2u} 1 β z 1 + z β = e 2 u
or
2 u = log β‘ ( 1 + z 1 β z ) whenceΒ followsΒ theΒ result. 2u = \log \left( \frac{1+z}{1-z} \right) \quad \text{whence follows the result.} 2 u = log ( 1 β z 1 + z β ) whenceΒ followsΒ theΒ result.
Pradeep Giri Academy Dr. Chand Ram
VIDEO It is not a single video but a playlist, and it contains two videos. When one video finishes, the next will play automatically.
Logarithmic Function:
If z = ( x + i y ) z = (x + iy) z = ( x + i y ) and w = ( u + i v ) w = (u + iv) w = ( u + i v ) be so related that e w = z e^w = z e w = z , then w w w is said to be a logarithm of z z z to the base e e e and is written as w = log β‘ e z β
β β
β β
β t e x t i w = \log_e z\; \; \; text{i} w = log e β z t e x t i .
Also
e w + 2 i n Ο = e w β
e 2 i n Ο = z [ β΅ e 2 i n Ο = 1 ] e^{w + 2in\pi} = e^w \cdot e^{2in\pi} = z \quad \left[ \because e^{2in\pi} = 1 \right] e w + 2 inΟ = e w β
e 2 inΟ = z [ β΅ e 2 inΟ = 1 ]
Thus,
log β‘ z = w + 2 i n Ο β
β β
β β
β β
β β
β ii \log z = w + 2in\pi \; \; \; \; \; \text{ii} log z = w + 2 inΟ ii
i.e., the logarithm of a complex number has an infinite number of values and is, therefore, a multi-valued function.
The general value of the logarithm of z z z is written as LogΒ z \text{Log } z LogΒ z (beginning with capital L L L ) so as to distinguish it from its principal value which is written as log β‘ z \log z log z .
This principal value is obtained by taking n = 0 n = 0 n = 0 in LogΒ z \text{Log } z LogΒ z .
Thus from (i) and (ii),
LogΒ ( x + i y ) = 2 i n Ο + log β‘ ( x + i y ) \text{Log } (x + iy) = 2in\pi + \log (x + iy) LogΒ ( x + i y ) = 2 inΟ + log ( x + i y )
Real and imaginary parts of Log ( x + i y ) (x + iy) ( x + i y ) .
LogΒ ( x + i y ) = 2 i n Ο + log β‘ ( x + i y ) \text{Log } (x + iy) = 2in\pi + \log (x + iy) LogΒ ( x + i y ) = 2 inΟ + log ( x + i y )
= 2 i n Ο + log β‘ [ r ( cos β‘ ΞΈ + i sin β‘ ΞΈ ) ] = 2in\pi + \log \left[ r (\cos \theta + i \sin \theta) \right] = 2 inΟ + log [ r ( cos ΞΈ + i sin ΞΈ ) ]
= 2 i n Ο + log β‘ ( r e i ΞΈ ) = 2in\pi + \log \left( r e^{i\theta} \right) = 2 inΟ + log ( r e i ΞΈ )
= 2 i n Ο + log β‘ r + i ΞΈ = log β‘ x 2 + y 2 + i [ 2 n Ο + tan β‘ β 1 ( y x ) ] = 2in\pi + \log r + i\theta = \log \sqrt{x^2 + y^2} + i \left[ 2n\pi + \tan^{-1} \left( \frac{y}{x} \right) \right] = 2 inΟ + log r + i ΞΈ = log x 2 + y 2 β + i [ 2 nΟ + tan β 1 ( x y β ) ]
PutΒ x = r cos β‘ ΞΈ , β y = r sin β‘ ΞΈ Β soΒ thatΒ r = x 2 + y 2 Β andΒ ΞΈ = tan β‘ β 1 ( y x ) \text{Put } x = r \cos \theta, \, y = r \sin \theta \text{ so that } r = \sqrt{x^2 + y^2} \text{ and } \theta = \tan^{-1} \left( \frac{y}{x} \right) PutΒ x = r cos ΞΈ , y = r sin ΞΈ Β soΒ thatΒ r = x 2 + y 2 β Β andΒ ΞΈ = tan β 1 ( x y β )
Real and imaginary parts of ( Ξ± + i Ξ² ) Ξ³ + i Ξ΄ (\alpha + i \beta)^{\gamma + i \delta} ( Ξ± + i Ξ² ) Ξ³ + i Ξ΄ .
( Ξ± + i Ξ² ) Ξ³ + i Ξ΄ = e ( Ξ³ + i Ξ΄ ) log β‘ ( Ξ± + i Ξ² ) = e ( Ξ³ + i Ξ΄ ) [ log β‘ r + i ( ΞΈ + 2 n Ο ) ] (\alpha + i \beta)^{\gamma + i \delta} = e^{(\gamma + i \delta) \log (\alpha + i \beta)} = e^{(\gamma + i \delta) [\log r + i(\theta + 2n\pi)]} ( Ξ± + i Ξ² ) Ξ³ + i Ξ΄ = e ( Ξ³ + i Ξ΄ ) l o g ( Ξ± + i Ξ² ) = e ( Ξ³ + i Ξ΄ ) [ l o g r + i ( ΞΈ + 2 nΟ )]
= e ( Ξ³ + i Ξ΄ ) [ log β‘ r + i ΞΈ ] = e [ Ξ³ log β‘ r β Ξ΄ ΞΈ ] e i [ Ξ΄ log β‘ r + Ξ³ ΞΈ + 2 n Ο Ξ³ ] = e^{(\gamma + i \delta) [\log r + i\theta]} = e^{[\gamma \log r - \delta \theta]} e^{i[\delta \log r + \gamma \theta + 2n\pi \gamma]} = e ( Ξ³ + i Ξ΄ ) [ l o g r + i ΞΈ ] = e [ Ξ³ l o g r β Ξ΄ ΞΈ ] e i [ Ξ΄ l o g r + Ξ³ ΞΈ + 2 nΟΞ³ ]
= e A [ cos β‘ B + i sin β‘ B ] = e^A [\cos B + i \sin B] = e A [ cos B + i sin B ]
where A = x log β‘ r β y ( 2 n Ο + ΞΈ ) A = x \log r - y(2n\pi + \theta) A = x log r β y ( 2 nΟ + ΞΈ ) and B = y log β‘ r + x ( 2 n Ο + ΞΈ ) B = y \log r + x(2n\pi + \theta) B = y log r + x ( 2 nΟ + ΞΈ ) .
β΄ \therefore β΄ the required real part = e A cos β‘ B e^A \cos B e A cos B and the imaginary part = e A sin β‘ B e^A \sin B e A sin B .
MKS Tutorials Dr.G.P.
VIDEO It is not a single video but a playlist, and it contains ten videos. When one video finishes, the next will play automatically.
Analytic Functions:
A function f ( z ) f(z) f ( z ) which is single-valued and possesses a unique derivative with respect to z z z at all points of a region R R R , is called an analytic function of z z z in that region.
An analytic function is also called a regular function or a holomorphic function.
A function which is analytic everywhere in the complex plane, is known as an entire function.
As derivative of a polynomial exists at every point, a polynomial of any degree is an entire function.
A point at which an analytic function ceases to possess a derivative is called a singular point of the function.
Thus if u u u and v v v are real single-valued functions of x x x and y y y such that β u / β x \partial u/\partial x β u / β x , β u / β y \partial u/\partial y β u / β y , β v / β x \partial v/\partial x β v / β x , β v / β y \partial v/\partial y β v / β y are continuous throughout a region R R R , then the Cauchy-Riemann equations
β u β x = β v β y and β u β y = β β v β x β
β β
β β
β β
β (1) \frac{\partial u}{\partial x} = \frac{\partial v}{\partial y} \quad \text{and} \quad \frac{\partial u}{\partial y} = - \frac{\partial v}{\partial x} \; \; \; \; \text{(1)} β x β u β = β y β v β and β y β u β = β β x β v β (1)
are both necessary and sufficient conditions for the function f ( z ) = u + i v f(z) = u + iv f ( z ) = u + i v to be analytic in R R R .
The real and imaginary parts of an analytic function are called conjugate functions.
The relation between two conjugate functions is given by the C-R equation (1).
Pradeep Giri Academy Mathematics Analysis
VIDEO It is not a single video but a playlist, and it contains six videos. When one video finishes, the next will play automatically.